Enzymatically Modified Low‐Density Lipoprotein Is Present in All Stages of Aortic Valve Sclerosis: Implications for Pathogenesis of the Disease. Issue 10 (16th October 2015) - Twardowski, Laura; Cheng, Fei; Michaelsen, Jens; Winter, Stefan; Hofmann, Ute; Schaeffeler, Elke; Müller, Simon; Sonnenberg, Maike; Steuer, Kristin; Ott, German; Schwab, Matthias; Franke, Ulrich F. W.; et al.
Abstract : Background: We have demonstrated previously that enzymatically degraded low‐density lipoprotein (eLDL) is an essential causative component for the initiation of atherosclerosis. Here, we investigated the different stages of human aortic valve sclerosis for the presence of eLDL and effectors of the innate immune system, as well as the interaction of eLDL with isolated valvular interstitial cells/myofibroblasts to discover possible pathways leading to aortic valve sclerosis. Methods and Results: Human aortic valvular tissue was obtained from 68 patients undergoing valve replacement surgery. Patients were classified into 3 groups (mild, moderate, or severe aortic valve sclerosis), and clinical data for statistical analysis were gathered from all patients. Immunohistochemical staining demonstrated extensive extracellular deposits of eLDL throughout all grades of aortic valve sclerosis. Complementary analysis of lipid composition revealed higher concentrations of the decisive components of eLDL (ie, unesterified cholesterol and linoleic acid) compared with internal control tissues. Further, the complement component C3d and terminal complement complexes colocalized with eLDL compatible with the proposal that subendothelially deposited eLDL is enzymatically transformed into a complement activator at early stages of valvular cusp lesion development. Gene expression profiles of proteases and complement components corroborated by immunohistochemistry demonstrated an upregulation of the protease cathepsin D (a possible candidate for LDL degradation to eLDL) and the complement inhibitor CD55. Surprisingly, substantial C‐reactive protein expression was not observed before grade 2 aortic valve sclerosis as investigated with microarray analysis, reverse transcription–polymerase chain reaction analysis, and immunohistochemistry. Finally, we demonstrated cellular uptake of eLDL by valvular interstitial cells/myofibroblasts. Conclusions: The present study is a startup of a hypothesis on the pathogenesis of aortic valve sclerosis declaring extracellular lipoprotein modification, subsequent complement activation, and cellular uptake by valvular interstitial cells/myofibroblasts as integral players.